Pengaruh Social Media Marketing dan Kredibilitas Influencer terhadap Keputusan Pembelian Sepatu Lokal (Ventela) Bali Melalui Consumer Engagement sebagai Variabel Mediasi - Nilna Muna; Nyoman Dordy Surya Divana Putra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research was conducted in Denpasar City at Ventela Bali, located on Serma Mendra Street, Denpasar, Bali. Ventela Bali operates as a distributor of local footwear products in Denpasar. The study aimed to analyze the influence of Social Media Marketing and Influencer Credibility on Purchase Decisions through Consumer Engagement at Ventela Bali. This study employed a quantitative research approach with a sample of 92 respondents. Both quantitative and qualitative data were utilized, obtained from primary and secondary sources. Data were collected through documentation, questionnaires, and online data searching. The data were analyzed using the Partial Least Squares (PLS) method with SmartPLS 4 software. The results revealed that Social Media Marketing had a positive and significant direct effect on the purchase decisions of Ventela local shoes. Influencer Credibility had a positive but insignificant direct effect on purchase decisions. Likewise, Consumer Engagement had a positive but insignificant direct effect on purchase decisions. Furthermore, Social Media Marketing had a positive and significant direct effect on Consumer Engagement, while Influencer Credibility also had a positive and significant direct effect on Consumer Engagement. Regarding the indirect effects, Consumer Engagement showed a positive but insignificant mediating role in the relationship between Social Media Marketing and Purchase Decisions. Similarly, Consumer Engagement demonstrated a positive but insignificant mediating role in the relationship between Influencer Credibility and Purchase Decisions at Ventela Bali.